Lectotypification of Actinodaphne lanata Meisn. (Lauraceae) and notes on its occurrence in the Western chats, India (Bangladesh Journal of Plant Taxonomy, 2017)
Not available.Keywords: Actinodaphne; Critically Endangered; Lauraceae; Lectotype; Southern Western Ghats.Bangladesh J. Plant Taxon. 24(1): 119123, 2017 (June)